A SEM-PLS ANALYSIS OF HYPERTENSION DETERMINANTS IN WEST JAVA, INDONESIA: SOCIO-ECOLOGICAL MODEL APPROACHES - Baliwati, Yayuk Farida; Laely, Putri Nur; Rusyda, Akifa Laila (Media Gizi Indonesia, 2025)
The second national highest prevalence of hypertension in 2018 was West Java, with a prevalence rate of 39.6%. The high prevalence of hypertension is driven by the interaction of multiple determinants, including consumption pattern (food intake and tobacco use), environmental status (primary health services and infrastructure) and socioeconomic status. The study aims to analyze the determinants of hypertension using socio-ecological approaches in West Java. The research design was an ecological study, using secondary data for 2019-2020 covering 26 districts or regencies in West Java. The total unit analysis was 52, regarding two years data analysis used. Analysis of data was performed using the partial least squares structural equation modeling (PLS-SEM) approach with bootstrap estimation. The result shows that all indicators of consumption pattern and primary health services and infrastructure variables are significant in forming a model. Findings also show that consumption patterns (intake of protein (meat, milk and eggs), sodium in spices, tobacco use (cigarettes)) and primary health services and infrastructure also directly affect hypertension, with coefficient value of 1.142 and 0.401, respectively. Socioeconomic status also indirectly affects hypertension through consumption variable and primary health service infrastructure variable. The SEM-PLS model built   strongly represents the determinants of hypertension in West Java, Indonesia based on the socio-ecological model Approaches (goodness-of fit value= 0.67). Strengthening food resources management and nutrition policies, including reducing sodium intake, and controlling tobacco use can lower risks, while improving healthcare access, infrastructure, and clean water supports hypertension prevention in West Java.